Histamine in the kidneys: what is its role in renal pathophysiology?. (15th April 2019) - Grange, Cristina; Gurrieri, Maura; Verta, Roberta; Fantozzi, Roberto; Pini, Alessandro; Rosa, Arianna Carolina
Abstract : Starting with a role for histamine role in renal haemodynamics, evidence has accumulated, over time, suggesting a wider range of actions on renal function and this has renewed interest in the pathophysiological role of histamine in the kidney. Here we provide an up‐to‐date review of this topic. As the kidney expresses enzymes that synthesize and metabolise histamine, along with its receptors, all the components for histaminergic transmission are present in this tissue. The distribution of histamine receptors matches a wide range of effects. We address the questions of the redundancy of H1 and H2 receptors in renal haemodynamics, the complementary role of H1 and H4 receptors in renal filtration and reabsorption, and the dichotomy between local and neuronal H1 and H3 receptors. Experimental models of renal disease raise the possibility of new therapeutic approaches based on histamine. The effects of histamine on renal function are not yet fully understood and their elucidation is still ongoing. Linked Articles: This article is part of a themed section on New Uses for 21st Century. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.3/issuetoc